Interconversion of Lewis acid and Brønsted acid catalysts in biomass-derived paraxylene synthesis. (14th December 2020) - Cui, Ziheng; Feng, Xinqiang; Li, Hui; Tan, Tianwei
Graphical abstract: Highlights: The water produced during the preparation of PX converts the L acid of WOx /SiO2 to B acid. [WO4 ] 2− site can be restored to Lewis acid by DMF hydrolysis reaction. Reaction network of WOx /SiO2 catalyzed DMF to prepare PX is constructed. The catalytic activity and selectivity under various temperatures are predicted by kinetic Monte Carlo simulations. Abstract: The change of acidity of catalyst site during the catalytic reaction may enforce great influence on the efficiency of catalyst. Here, the WOx catalyst highly dispersed on surface of SiO2 molecular sieve is synthesized, which is found to possess strong Lewis acidity and great catalytic ability for producing paraxylene through the Diels-Alder cycloaddition reaction of 2, 5-dimethylfuran and ethylene. Based on a comprehensive density functional theory study, we find that the water generated during the reaction can convert the Lewis acid sites into Brønsted acid sites, thereby, turn the Lewis acid catalytic reaction into the Brønsted acid assisted reaction. The kinetic Monte Carlo (kMC) simulations reveal that the selectivity of PX relative to the by-product 2, 5-hexanedione increases with reaction temperature, which is consistent with the experimental observation. The unravelling of the interconversion of Lewis acid and Brønsted acid gives us new insight of the mechanism of acid-catalytic reactions.